Creating a Social Wasteland? Non-Traditional Agricultural Exports and Rural Poverty in Ecuador - Korovkin, Tanya (European Review of Latin American and Caribbean Studies, 2005)
Neoliberal economic policies in Latin America have resulted in the rapid growth of nontraditional agricultural exports (NTAE). This growth is often seen as contributing to the alleviation of rural poverty. The paper examines this view with the focus on Ecuador, using the World Bank’s definition poverty as a reference. It is argued that the flower export expansion has created employment opportunities but did not allow the rural poor to raise themselves above the poverty line. Moreover, flower employment has undermined the pre-existing social networks and community organizations, increasing the levels of insecurity among rural families and undermining their ability to influence the processes of decision making. Resumen: Creando un páramo social? Exportaciones agrícolas no-tradicionales y pobreza rural en EcuadorLas políticas económicas neo-liberales en América Latina han resultado en el rápido crecimiento de las exportaciones agrícolas no tradicionales (EANT), lo que es considerado a menudo como un alivio de la pobreza rural. En este artículo se estudia esta visión para el caso de Ecuador, utilizando como referencia la definición de pobreza del Banco Mundial. Aunque se dice que la expansión en la exportación de flores ha creado oportunidades de empleo, no ha logrado que los pobres rurales crucen la línea de la pobreza. Además, el empleo en este sector ha socavado las redes sociales y organizaciones comunitarias anteriores, elevando los niveles de inseguridad entre las familias rurales y minando su capacidad de intervención en el proceso de toma de decisiones.